Endocannabinoid receptor 1 gene variations increase risk for obesity and modulate body mass index in European populations - Benzinou, Michael; Chèvre, Jean-Claude; Ward, Kirsten J; Lecoeur, Cécile; Dina, Christian; Lobbens, Stephane; Durand, Emmanuelle; Delplanque, Jérome; Horber, Fritz F; Heude, Barbara; Balkau, Beverley; Borch-Johnsen, Knut; et al. (Human molecular genetics, 2008)
The therapeutic effects of cannabinoid receptor blockade on obesity-associated phenotypes underline the importance of the endocannabinoid pathway on the energy balance. Using a staged-approach, we examined the contribution of the endocannabinoid receptor 1 gene (CNR1) on obesity and body mass index (BMI) in the European population. With the input of CNR1 exons and 3' and 5' regions sequencing and HapMap database, we selected and genotyped 26 tagging single-nucleotide polymorphisms (SNPs) in 1932 obese cases and 1173 non-obese controls of French European origin. Variants that showed significant associations (P < 0.05) with obesity after correction for multiple testing were further tested in two additional European cohorts including 2645 individuals. For the identification of the potential causal variant(s), we further genotyped SNPs in high linkage disequilibrium (LD) with the obesity-associated variants. Of the 25 successfully genotyped CNR1 SNPs, 12 showed nominal evidence of association with childhood obesity, class I and II and/or class III adult obesity (1.16 < OR < 1.40, 0.00003 < P < 0.04). Intronic SNPs rs806381 and rs2023239, which resisted correction for multiple testing were further associated with higher BMI in both Swiss obese subjects and Danish individuals. The genotyping of all know variants in partial LD (r(2) > 0.5) with these two SNPs in the initial case-control study, identified two better associated SNPs (rs6454674 and rs10485170). Our study of 5750 subjects shows that CNR1 variations increase the risk for obesity and modulate BMI in our European population. As CB1 is a drug target for obesity, a pharmacogenetic analysis of the endocannabinoid blockade obesity treatment may be of interest to identify best responders.